ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CSR - Lovink Angel Dwi Karina; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2013)
The aim of this study is to obtain an empirical evidence about factor that affect CSR disclosure in manufacture firm annual report’s. The factors that used in this study such as : government ownership, foreign ownership, company type, industry size, profitability and also government leverage as an additional variable. Measurement of Corporate Social Responsibility is based on corporate social reporting categories that used to calculate the Corporate Social Responsibility Index (CSRI) as seen from the company's annual report.Populations in this study are all manufacture companies that listed in Indonesian stock exchange in 2011. The sampling method in this study is purposive sampling. The total number of samples in this study were 92 research samples. The analytical techniques was conducted by multiple regression method and also classical assumption test.The analysis showed that government ownership and company size significantly positive influence the CSR disclosure in Indonesia. Meanwhile, foreign ownership, industry type, profitability, and leverage were not significantly positive affect the CSR disclosure in Indonesia.